Impact of livelihood development on CO2 emissions: empirical evidence from Yangtze River delta urban agglomeration - Zhu, Zhiming; Lin, Wenxue (Frontiers in Environmental Science, 2025)
In the context of the “dual-carbon” goal and the building of a moderately prosperous society, it is of great significance to explore in depth the impact of livelihood development on urban carbon emissions. This paper uses the Human Development Index (HDI) as a proxy for assessing livelihood development. Based on the data of a panel of 41 cities in the Yangtze River Delta urban agglomeration from 2000 to 2021, this study constructs the fixed effect model, mediating effect and moderating effect models to empirically test the impact of livelihood development on CO2 emissions from energy consumption and its mechanism. The HDI of the Yangtze River Delta urban agglomeration exhibited a steady increase from 0.64 in 2000 to 0.81 in 2021, marking a significant leap from a moderate to a very high level of human development, with an overall increase of 27.41%. The results show that there is a significant inverted U-shaped relationship between livelihood development and urban CO2 emissions. Innovation inputs play an intermediary role and investment intensity positively moderates the inverted U-shaped relationship between livelihood development and CO2 emissions. Moreover, the analysis finds that the impact of livelihood development on CO2 emissions varies significantly among regions with different geographic locations and resource endowments. The inverted U-shaped relationship between livelihood development and CO2 emissions is more pronounced in central cities and non-resource-based cities. The above research results show that urban carbon emissions can be effectively reduced by optimizing livelihood development, and provide a scientific basis for achieving the target of carbon peak. This study reveals the relationship between livelihood development and CO2 emissions, provides a new perspective for sustainable urban development, and provides a basis for promoting the simultaneous realization of livelihood development and carbon emission reduction targets in the Yangtze River Delta urban agglomeration.